Brand Marketing Strategies of Trade Enterprises on Social Media Platforms - FAYVISHENKO, Diana; LIULCHAK, Zoreslava; MOHYLOVA, Anastasiia; YAROVENKO, Tetiana; LORVI, Iryna; ALDANKOVA, Halyna (Theoretical and Practical Research in Economic Fields, 2024)
Social media platforms are an important marketing tool for business promotion, in particular for increasing user engagement, coverage, awareness, and satisfaction. Marketing efficiency in social networks is significantly dependent on the choice and implementation of the brand strategy, which makes the studied theme relevant. The paper aims to study key factors of influence on the selection and implementation of SMM strategies. The study used statistical analysis methods, forecasting method, and comparative and descriptive methods. The results of the conducted study showed that the SMM market is rapidly developing, and this tendency is going to be preserved in the coming years. In particular, it is expected that the number of social network users will reach 5.85 billion people in 2027, while global advertising costs in social networks will amount to approximately 247.32 billion USD in the same year. The work has found exceeding advertising costs in social networks over the revenues from sales in the USA. This may be explained by the fact that marketing in social networks is, above all, oriented toward social objectives rather than an increase in sales volume or profit growth. Considering the conducted analysis, the approach to the formation of the stages of brand strategy on social media platforms with consideration of metrics systems was offered. The received results can be used by trade enterprises in the process of development of promotional campaigns in social networks.